Electrochemical Detection of Glutathione Using Redox Indicators - Pacsial-Ong, Eden Joy (2006)
The nucleophilic addition of the aminothiols homocysteine (HCY), cysteine (CYS), and glutathione (GSH) to the electrogenerated quinone of fluorone black (1) via the ECE mechanism is reported. It is demonstrated that 1 selectively reacts with GSH to form the bis-GSH adduct, 1–(GSH)(2), while only the monothiol adducts were generated in the presence of HCY and CYS (1–HCY and 1–CYS, respectively). The more anodic E(pa) of 1–(GSH)(2) relative to 1 and 1–GSH (ΔE(pa) ~ +0.14) is the voltammetric signature that allows the discrimination of GSH from HCY and CYS. It is also shown that the presence of structurally similar aminothiols–HCY and CYS–posed no interference to the signature voltammetric response of 1–(GSH)(2).